Fiqh Muamalah and Sharia Marketing Strategy: Value Integration for Optimizing Emotional and Commercial Markets Islamic Banking in Indonesian - Tentiyo Suharto; Sukiman Sukiman; Maryam Batubara (Nomico, 2026)
This study aims to analyze problems and formulate a sharia marketing strategy for Islamic banking in Indonesia, integrating the emotional (religious-spiritual) and commercial (rational-economic) markets based on the perspective of maqasid al-sharia. The background of the study indicates that although the Islamic banking industry has experienced significant growth, its market share remains relatively low due to the suboptimal integration of sharia compliance, modern marketing values, and digital transformation. This study uses a mixed methods approach supported by the Analytic Network Process (ANP) to determine the most relevant and beneficial marketing strategy priorities. The results indicate that an effective sharia marketing strategy must combine the emotional dimensions of trust, blessings, and sharia compliance with the commercial dimensions of efficiency, service quality, product innovation, and competitiveness. The main findings revealed that digital marketing and social media optimization are the highest priority strategies, followed by partnerships in the commercial market segment, utilization of sharia fintech, optimization of contracts in sharia banking fiqh, partnerships in the emotional market segment, and community-based or people-based marketing programs. This integration of emotional and commercial markets confirms that Sharia marketing is not simply a business instrument, but rather a muamalah practice oriented toward the realization of the maqasid al-Shariah, specifically the protection of religion (hifz al-din) and the protection of property (hifz al-mal). Therefore, marketing activities are not exploitative, but rather promote public or customer trust, financial inclusion, and the ethical and competitive sustainability of Sharia banking.